Locating Geodiversity Hotspots through Grid-Based Spatial Indexing: Lombok Island, Indonesia - Gathot Harbowo, Danni; Siringoringo, Luhut Pardamean (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Locating geodiversity hotspots across large areas poses a challenge for further geopark development in Indonesia, especially on Lombok Island, which spans 5,435 km². A geodiversity hotspot is an area rich in unique geological features that need to be determined. Therefore, this study's objective is to track and assess the potential of geodiversity on Lombok Island. The methods employed a grid-based spatial indexing method to pinpoint potential geodiversity hotspots in Lombok. The entire island was covered using 238 grids of 5×5 km² for this study. The technique applied these equal weight parameters: relative drainage density (20%), diversity of topographical slope (20%), elevation (20%), diversity of geological formation (20%), and soil characteristics (20%). The identified geodiversity hotspots were validated through ground checking. The results show significant geodiversity hotspots: Gangga (116°12'13.122"E;8°21'24.154"S), Sikur (116°24'32.015"E;8°29'23.597"S), Bayan (116°32'33.211"E;8°16'22.39"S), Sembalun (116°29'18.063"E;8°23'22.156"S), Sambelia (116°35'40.856"E;8°24'1.371"S), and Gerung-Kuripan (116°8'20.085"E;8°41'46.513"S). These hotspots showcase a range of lithologies from the Oligo-Miocene to the Plio-Pleistocene, along with terrestrial and marine fossils, minerals, geothermal activities associated with the Rinjani Volcano, and diverse soil types that support rich biodiversity. The dense drainage systems in these regions create stunning waterfalls and distinct elevational ecosystems. Tourism is primarily concentrated in well-known sites like Sembalun and Gerung-Kuripan, while lesser-known areas such as Sambelia, Gangga, Sikur, and Bayan remain underexplored. The natural drainage systems in these hotspots play a crucial role in hydrology and contribute to the beautiful landscapes. This study concludes that Lombok Island has six significant geodiversity hotspots, which hold geological importance for supporting the geoheritage of the Rinjani-Lombok UNESCO Global Geopark. The findings contribute to promoting local development by integrating cultural aspects and ensuring sustainability in line with global sustainable development goals. Additionally, the study provides new insights into the geotourism potential that can support sustainable development within the Rinjani-Lombok UNESCO Global Geopark.